In the Theory Lunch of the last week, James Chapman talked about the MU puzzle from Douglas Hofstadter’s book Gödel, Escher, Bach. This puzzle is about a string rewriting system. James presented a Haskell program that computes derivations of strings. Inspired by this, I wrote my own implementation, with the goal of improving efficiency. This blog post presents this implementation. As usual, it is available as a literate Haskell file, which you can load into GHCi.
Let me first describe the MU puzzle shortly. The puzzle deals with strings that may contain the characters , , and . We can derive new strings from old ones using the following rewriting system:
The question is whether it is possible to turn the string into the string using these rules.
You may want to try to solve this puzzle yourself, or you may want to look up the solution on the Wikipedia page.
The code is not only concerned with deriving from , but with derivations as such.
We define the type
Sym of symbols and the type
Str of symbol strings:
data Sym = M | I | U deriving Eq type Str = [Sym] instance Show Sym where show M = "M" show I = "I" show U = "U" showList str = (concatMap show str ++)
Next, we define the type
Rule of rules as well as the list
rules that contains all rules:
data Rule = R1 | R2 | R3 | R4 deriving Show rules :: [Rule] rules = [R1,R2,R3,R4]
We first introduce a helper function that takes a string and returns the list of all splits of this string. Thereby, a split of a string
str is a pair of strings
str2 such that
str1 ++ str2 == str. A straightforward implementation of splitting is as follows:
splits' :: Str -> [(Str,Str)] splits' str = zip (inits str) (tails str)
The problem with this implementation is that walking through the result list takes quadratic time, even if the elements of the list are left unevaluated. The following implementation solves this problem:
splits :: Str -> [(Str,Str)] splits str = zip (map (flip take str) [0 ..]) (tails str)
Next, we define a helper function
replace. An expression
replace old new str yields the list of all strings that can be constructed by replacing the string
replace :: Str -> Str -> Str -> [Str] replace old new str = [front ++ new ++ rear | (front,rest) <- splits str, old `isPrefixOf` rest, let rear = drop (length old) rest]
We are now ready to implement the function
apply, which performs rule application. This function takes a rule and a string and produces all strings that can be derived from the given string using the given rule exactly once.
apply :: Rule -> Str -> [Str] apply R1 str | last str == I = [str ++ [U]] apply R2 (M : tail) = [M : tail ++ tail] apply R3 str = replace [I,I,I] [U] str apply R4 str = replace [U,U]  str apply _ _ = 
Now we want to build derivation trees. A derivation tree for a string
str has the following properties:
- The root is labeled with
- The subtrees of the root are the derivation trees for the strings that can be generated from
strby a single rule application.
- The edges from the root to its subtrees are marked with the respective rules that are applied.
We first define types for representing derivation trees:
data DTree = DTree Str [DSub] data DSub = DSub Rule DTree
Now we define the function
dTree that turns a string into its derivation tree:
dTree :: Str -> DTree dTree str = DTree str [DSub rule subtree | rule <- rules, subStr <- apply rule str, let subtree = dTree subStr]
A derivation is a sequence of strings with rules between them such that each rule takes the string before it to the string after it. We define types for representing derivations:
data Deriv = Deriv [DStep] Str data DStep = DStep Str Rule instance Show Deriv where show (Deriv steps goal) = " " ++ concatMap show steps ++ show goal ++ "\n" showList derivs = (concatMap ((++ "\n") . show) derivs ++) instance Show DStep where show (DStep origin rule) = show origin ++ "\n-> (" ++ show rule ++ ") "
Now we implement a function
derivs that converts a derivation tree into the list of all derivations that start with the tree’s root label. The function
derivs traverses the tree in breadth-first order.
derivs :: DTree -> [Deriv] derivs tree = worker [(,tree)] where worker :: [([DStep],DTree)] -> [Deriv] worker tasks = rootDerivs tasks ++ worker (subtasks tasks) rootDerivs :: [([DStep],DTree)] -> [Deriv] rootDerivs tasks = [Deriv (reverse revSteps) root | (revSteps,DTree root _) <- tasks] subtasks :: [([DStep],DTree)] -> [([DStep],DTree)] subtasks tasks = [(DStep root rule : revSteps,subtree) | (revSteps,DTree root subs) <- tasks, DSub rule subtree <- subs]
Finally, we implement the function
derivations which takes two strings and returns the list of those derivations that turn the first string into the second:
derivations :: Str -> Str -> [Deriv] derivations start end = [deriv | deriv@(Deriv _ goal) <- derivs (dTree start), goal == end]
You may want to enter
derivations [M,I] [M,U,I]
at the GHCi prompt to see the
derivations function in action. You can also enter
derivations [M,I] [M,U]
to get an idea about the solution to the MU puzzle.